If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 + -3g = 8 Solving 26 + -3g = 8 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-26' to each side of the equation. 26 + -26 + -3g = 8 + -26 Combine like terms: 26 + -26 = 0 0 + -3g = 8 + -26 -3g = 8 + -26 Combine like terms: 8 + -26 = -18 -3g = -18 Divide each side by '-3'. g = 6 Simplifying g = 6
| (3i+2j)(7i+9j)= | | 56=-28n | | x+2=3(82-x) | | 3(x+1)(x+1)-(x+3)(2x+2)=0 | | 7x-2=7x+28 | | 8-6x=14-7 | | -8y+32=5-7y | | (x+4)(x+4)-(3x-7)(3x-7)=0 | | 6x+27=-38+47 | | 1.5x-0.33x+0.33+4x+8=180 | | Pi*49= | | ln(x+2)+ln(2x+2)=ln(40) | | ln(x+2)+ln(2x+2)= | | 3(v+8)-5v=14 | | 7(-3y+2)=3(8+7y) | | 6a+b=-3 | | 24-3x=9 | | (9x+7)-(3x-2)= | | 9a+3b+c=4 | | 12-10x=122-45x | | 8y+7=-6y+2 | | 10+4x=3(7x-4)+5x | | -21p^2-24p=12 | | (-x^5)(-x)= | | 10x+2=-2+4 | | 2kx*2kx=0 | | (3x+9)+(6x+7)= | | 5x+10=4x+15 | | 6x+10y+11=0 | | x^2+2kx-7=0 | | -10p+3(8+8n)=-6(n-4) | | 137-5x=-58-8x |